War and Peace in Africa’s Great Lakes Region
XVIII, 148 p. 1 illus. in color.
Keywords: The book probes major security and governance trends in Africa’s Great Lakes region since the 1990s. It examines political dynamics in key states – Burundi, the DRC, Rwanda, and Uganda – as well as the role of international actors such as the AU, the EU, and the UN, thereby providing a unique perspective on efforts towards regional peace and prosperity. The authors suggest that while the region has made tremendous progress, it faces continuing challenges (including reversals in governance) that threaten future regional security. .